Great events. - Salem Press (Pasadena, Calif. : Salem Press, 1992)
Surveys significant events in the history of civil rights, military conflicts, economics, international relations, legislation, and social reform in the twentieth century.
1. 1900-1916 -- 2. 1916-1930 -- 3. 1931-1939 -- 4. 1939-1947 -- 5. 1948-1960 -- 6. 1960-1968 -- 7. 1968-1977 -- 8. 1977-1982 -- 9. 1982-1988 -- 10. 1988-1992 -- 11. 1992-1993 -- 12. 1993-1994 -- 13. 1994-1995.
"A Magill book from the editors of Salem Press."
Includes indexes.
Keywords: History, Modern -- 20th century -- Juvenile literature; History, Modern -- 20th century